Effect of nitrogen application on nitrogen leaching pattern and leaching loss from drip irrigated cotton fields in Southern Xinjiang - Honghong Ma; Zhiying Yang; Shenghai Pu; Xianglin Wu; Zeyu Wang; Xingwang Ma; Tao Yang (Environmental Research Communications, 2023)
Farmers provided excessive nitrogen fertilizer to obtain high cotton yield in Xinjiang, Northwest China. Although drip irrigation could save water resources and improve nitrogen use efficiency, it is not known if leaching is occurring or not and whether leaching will harm the water environment under different nitrogen application. The purpose of our study was to estimate the effect of different nitrogen (N) application on the N leaching loss in drip irrigated cotton fields in South Xinjiang. A field experiment was conducted with N application rates of 317(N317), 395(N395) and 476(N476) kg hm ^−2 from 2021 to 2022. The characteristics of N pattern and leaching amount were analyzed. The concentration of NO _3 - and total nitrogen in the leaching water significantly decreased with the decrease of N application. The proportion of NO _3 –to total nitrogen reached the highest values of 51.52%–58.16%, 49.53%–56.91%, and 57.52%–62.87% at bud, flower, and boll stages of cotton, respectively. Moreover, the proportion of NO _3 – to total nitrogen remained at a stable level, which indicated that NO _3 –was the main pattern of N leaching. The N loss in the treatment N395 and N317 was 79.67% and 67.48% of that in the N476 treatment (1.23 kg hm ^−2 ), while the yield was 120.56% and 112.46% of that in the N476 treatment. Compared with conventional fertilizer application (476 kg hm ^−2 ), the reasonable N fertilizer application would not only reduce the amount of N leaching, but also increase the cotton yield.